The Influence Of Environmental Performance And Corpo-rate Social Responsibility On The Financial Performance - Afani, Amirah; Atmini, Sari (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This study is motivated by the growing importance of sustainability performance in business, especially in the mining sector, which poses significant environmental risks. The purpose of this research is to examine the effect of environmental performance and Corporate Social Responsibility (CSR) on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. Environmental performance is measured using the PROPER rating issued by the Ministry of Environment and Forestry (KLHK), while CSR is measured by the number of items disclosed in accordance with the Global Reporting Initiative (GRI) 2021 guidelines. Financial performance is assessed using the Return on Assets (ROA) indicator. This study adopts a quantitative approach using multiple linear regression analysis, based on secondary data obtained from annual reports, sustainability reports, and PROPER documents. The results indicate that environmental performance positively affects financial performance, whereas CSR disclosure has no impact on it. These findings suggest that compliance with environmental standards can enhance a company’s financial outcomes, but CSR disclosure alone is insufficient to generate direct financial benefits. The study underscores the need for companies to strengthen the substance of their CSR initiatives and integrate environmental sustainability into long-term business strategies.